Organizational Change: Employees Reaction Towards It - Furxhi, Gentisa; Prof.as.dr.Sonela Stillo; Doc. Marinela Teneqexhi (European Journal of Multidisciplinary Studies, 2016)
The organizations, in the present days,are facing a dynamic environment which makes that no organization is immune towards change. Technological changes, innovations in communication, movements in the job market, globalization, make the organization face continuous challenges regarding competition, general non-stability of the macro-environment, merging and re-engineering of the work processes. To face these challenges, the organization reassesses the strategies, structure, policies, actions, processes and their culture. So the organizational change (OC) is inevitable in the environment where the organizations operate. Organizational change can be a very small change (additional) or it can be fundamental (transformative). Regardless of the form, function or size that the organizatioal change can make, there is an agreement between the community of the researchers that the pace of the organizational change has never been as high as in our days and it must be considered as a “feature which is present in the organizational life both in the operational level as well as in the strategic level” (By, 2005). Researchers already see the organizational change as a feature, present and continuous of the organizational life, inconsistent with the previous conceptualism that viewed the organizations as relatively stable systems, which developed over time through additional planned changes, which took place in regular and predicted phases (Burnes, 2004; Cummings -Worley, 2009). The famous expression “organizations don’t change, people do”, creates the need for change agents to understand that employees have different reactions to change initiative, because they have different personal experiences, motivation levels, socio-demographic characteristics, knowledges, values and different behavior models